Mass Trapping and Classical Biological Control of Rhynchophorus palmarum L. 1794 (Coleoptera: Curculionidae). A hypothesis based in morphological evidences. - Miguens, Flávio Costa; de Magalhães, Jorge André Sacramento; de Amorim, Livia Melo; Goebel, Viviane Rossi; Le Coustour, Nicola; Lummerzheim, Marie; Moura, José Inácio Lacerda; Costa, Rosane Motta (EntomoBrasilis, 2011)
Palm weevils have been reported as a pest and red ring nematode vectors for several palms of the Arecaceae family. Rhynchophorus palmarum L (Coleoptera: Curculionidae) is a pest for coconut crop and other palms. It is vector of Bursaphelencus cocophilus (Cobb) Baujard (Nematoda) etiological agent of Red Ring disease and other nematodes. Current methods recommended use of enemies and parasites in integrated pest management of Rhynchophorinae. In addition, mass trap reduce environmental damage. The objectives of our study on coconut plantations were: (1) to determine the efficiency of low expensive kariomones traps and (2) low expensive kariomones and pheromones traps using adult males; and (3) to examine R. palmarum using light and scanning electron microscopy searching for ectoparasites which can be proposed in integrated pest management. Handmade kariomones mass traps were efficient to R. palmarum and other Curculionidae capture but kariomones plus adult male R. palmarum was maintained inside trap enhanced its attractiveness for this palm weevil and Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae). R. palmarum presented occasionally fungal infection. In contrast, mites infested more than 50% of palm weevils. Infestation level was always high. Surface morphology of the mites and its interaction with R. palmarum were briefly described. All stages of ectoparasites life cycle were observed onto weevil elytra compartments. In this way, morphological evidences suggest the hypothesis of these mites as used as biological control agent in R. palmarum integrated pest management. Coleta Massal e Controle Biológico de Rhynchophorus palmarum L: Uma hipótese baseada me evidências morfológicas Resumo. Coleópteros têm sido descritos como pragas e vetores de nematódeos causadores de Anel Vermelho em diversas palmeiras da família Arecaceae. Rhynchophorus palmarum L (Coleoptera: Curculionidae) é uma praga que afeta a cocoicultura e outras palmeiras; e, vetor de Bursaphelencus cocophilus (Cobb) Baujard (Nematoda), agente etiológico de Anel Vermelho e de outros nematódeos. Atualmente, recomenda-se o emprego de inimigos naturais e parasitas no manejo integrado de pragas; dentre elas, Rhynchophorinae. Armadilhas de coleta massal são recomendadas no manejo integrado de pragas. Nosso estudo relata, na cocoicultura, a eficiência de armadilhas artesanais de baixo custo e a utilização cariomônios (toletes de cana-de-açúcar) e cariômonios mais feromônios (toletes de cana-de-açúcar e machos adultos de R. palmarum) como atrativos nas armadilhas. Ácaros ectoparasitas foram identificados nestes coleópteros, por microscopia, que podem ser propostos como parte do manejo integrado desta praga. Armadilhas de coleta massal com cariômonios foram eficientes na captura de R. palmarum e outros Curculionidae. No entanto, armadilhas de coleta massal com cariômonios e feromônios aumentaram a atratividade, em relação às primeiras, para este Coleoptera e Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae). Eventualmente, exemplares de R. palmarum apresentavam infecção fúngica. Ácaros ectoparasitas infestavam mais de 50% dos exemplares de R. palmarum. A microanatomia destes ácaros e sua interação com R. palmarum foi preliminarmente descrita. Todos os estágios do ciclo de vida destes ácaros foram identificados no compartimento dos élitros. As evidências morfológicas suportam a hipótese de que estes ácaros podem ser empregados no controle biológico de R. palmarum em um programa de manejo integrado.